Philosophy at the Edge of Chaos : Gilles Deleuze and the Philosophy of Difference. - Bell, Jeffrey A. (Heritage., 2006)
Far from being a philosopher who turns his back on what is taken to be a mistaken metaphysical tradition, Bell argues that Deleuze is best understood as a thinker who endeavoured to continue the work of traditional metaphysics and philosophy.